Serum short chain fatty acids mediate hippocampal BDNF and correlate with decreasing neuroinflammation following high pectin fiber diet in mice - Church, Jamie S.; Bannish, Jane A. M.; Adrian, Leighelle A.; Rojas Martinez, Kimberly; Henshaw, Asari; Schwartzer, Jared J. (Frontiers in Neuroscience, 2023)
Dietary components, such as prebiotic fiber, are known to impact brain chemistry via the gut-brain axis. In particular, short chain fatty acids (SCFAs) generated from excessive soluble fiber consumption are thought to impact neuroimmune signaling and brain function through increased production of neurotropic factors. Given reports that high dietary fiber intake is associated with increased mental health and improved quality of life scores, we set out to identify whether changes in SCFA levels as a result of a high soluble fiber diet mediate hippocampal neuroinflammation and brain derived neurotrophic factor (BDNF) in mice. To test this, adult male and female C57BL/6 mice were fed a one-month high pectin fiber or cellulose-based control diet. Following one month of excessive pectin consumption, serum SCFAs were measured using gas chromatography–mass spectrometry (GC-MS) and hippocampal cytokines and BDNF were assessed via multiplex magnetic bead immunoassay. Pectin-based fiber diet increased circulating acetic acid in both sexes, with no effect on propionic or butyric acid. In the hippocampus, a high fiber diet decreased TNFα, IL-1β, IL-6, and IFNγ and increased BDNF levels. Furthermore, increased SCFA levels were inversely correlated with neuroinflammation in the hippocampus, with acetic acid revealed as a strong mediator of increased BDNF production. Collectively, these findings highlight the beneficial effects of fiber-induced molecular changes in a brain region known to influence mood- and cognition-related behaviors. Dietary composition should be considered when developing mental health management plans for men and women with an emphasis on increasing soluble fiber intake.